Analisis Penerimaan Devisa Sektor Pariwisata dan Faktor-Faktor Yang Mempengaruhi di Provinsi Jawa Timur - Huda, Syamsul (Jurnal Aplikasi Manajemen, 2009)
Research is finding out total of foreign tourists, total of tourism object, total of hotel, total of travel bureau, length of stay in average of foreign tourists, average expenses of tourists and United States Dollar rate of exchange that influence tourism sector foreign exchange acceptance. This research is using data that obtained from first level tourism agency since 1993 until 2007. Data is analyzed by using multiple linear regression analysis with F-test and t-test. Conclusion of this research is that simultaneously number of tourists (X1), number of tourism object (X2), number of hotel (X3), travelling bureau (X4), length of stay in average (X5), tourists expenses average (X6), and United States dollar rate of exchange (X7) have significant influence to foreign exchange acceptance in tourism sector (Y). This statement is proved with F-test. Meanwhile examination partially with t-test stated that free variables have significant influence to foreign exchange acceptance in tourism sector (Y), those are number of tourists (X1), number of hotel (X3), travelling bureau (X4), length of stay in average (X5), tourists expenses average (X6), and United States dollar rate of exchange (X7), meanwhile variable of number of tourism object has no significant influence the foreign exchange acceptance in tourism sector (Y).